Listeria meningitis complicating a patient with ulcerative colitis on concomitant infliximab and hydrocortisone. (November 2016) - Parihar, V.; Maguire, S.; Shahin, A.; Ahmed, Z.; O'Sullivan, M.; Kennedy, M.; Smyth, C.; Farrell, R.
Abstract Infliximab, a monoclonal antibody directed against tumour necrosis factor, is an effective therapy for moderate-to-severe ulcerative colitis and Crohn's disease. Uncommonly, serious opportunistic infections have occurred in patients after infliximab administration. Here, we describe meningitis caused byListeria monocytogenes developing in a 37-year-old man with ulcerative colitis refractory to intravenous corticosteroids 10 days after receiving his first infusion of infliximab. With the increasing use of tumour necrosis factor-α-neutralizing agents, clinicians should be aware of the risk of opportunistic infections caused byL. monocytogenes in patients with inflammatory bowel disease following infliximab treatment. The half-life of infliximab is 9.5 days; therefore, patients tend to be more susceptible in the immediate period following infusion. Patients receiving anti-TNF therapy should be advised to avoid foods such as soft cheeses and unpasteurized dairy products.